2022
DOI: 10.3389/fbiom.2022.989708
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive potential evaluation of synovial fluid mesenchymal stem cells grown on 3D scaffolds as an alternative source of MSCs for osteoarthritis cartilage studies

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disease, leading cause of disability in older adults and leads to pain, reduced mobility, and decreased quality of life. Mesenchymal stem cells (MSC) - based therapies are the precursor to all tissues within a joint and their potential in regeneration is complemented by a modulation of the local inflammatory response. The use of MSCS-based therapy for regenerative medicine, specifically OA, is challenged by the need to investigate the ideal MSC source, establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…For this, they are studied for possible applications in osteoarthritis therapy by intra-articular injection [ 91 ] and in cartilage and meniscus regeneration. The promising potential of SM-MSCs in the treatment of osteoarthritis, which is caused by joint degradation with increasing age and has a higher incidence in females, has increased in the last decade [ 92 ]. Several studies reported a reversed osteoarthritis process, improvement of joint motility, cartilage quality, and pain relief [ 93 , 94 , 95 , 96 ].…”
Section: Tissue Source-dependent Heterogeneitymentioning
confidence: 99%
“…For this, they are studied for possible applications in osteoarthritis therapy by intra-articular injection [ 91 ] and in cartilage and meniscus regeneration. The promising potential of SM-MSCs in the treatment of osteoarthritis, which is caused by joint degradation with increasing age and has a higher incidence in females, has increased in the last decade [ 92 ]. Several studies reported a reversed osteoarthritis process, improvement of joint motility, cartilage quality, and pain relief [ 93 , 94 , 95 , 96 ].…”
Section: Tissue Source-dependent Heterogeneitymentioning
confidence: 99%